IL‐1β/IL‐1R1 signaling induced by intranasal lipopolysaccharide infusion regulates alpha‐Synuclein pathology in the olfactory bulb, substantia nigra and striatum. (4th August 2020) - Niu, Haichen; Wang, Qian; Zhao, Weiguang; Liu, Jianxin; Wang, Deguang; Muhammad, Bilal; Liu, Xiaoyu; Quan, Ning; Zhang, Haoyu; Zhang, Fang; Wang, Yong; Li, Haiying; et al.
Abstract: Olfactory dysfunction is one of the early symptoms seen in Parkinson's disease (PD). However, the mechanisms underlying olfactory pathology that impacts PD disease progression and post‐mortem appearance of alpha‐Synuclein (α‐Syn) inclusions in and beyond olfactory bulb in PD remain unclear. It has been suggested that environmental toxins inhaled through the nose can induce inflammation in the olfactory bulb (OB), where Lewy body (LB) is the first to be found, and then, spread to related brain regions. We hypothesize that OB inflammation triggers local α‐Syn pathology and promotes its spreading to cause PD. In this study, we evaluated this hypothesis by intranasal infusion of lipopolysaccharides (LPS) to induce OB inflammation in mice and examined cytokines expression and PD‐like pathology. We found intranasal LPS‐induced microglia activation, inflammatory cytokine expression and α‐Syn overexpression and aggregation in the OB via interleukin‐1β (IL‐1β)/IL‐1 receptor type I (IL‐1R1) dependent signaling. In addition, an aberrant form of α‐Syn, the phosphorylated serine 129 α‐Syn (pS129 α‐Syn), was found in the OB, substantia nigra (SN) and striatum 6 weeks after the LPS treatment. Moreover, 6 weeks after the LPS treatment, mice showed reduced SN tyrosine hydroxylase, decreased striatal dopaminergic metabolites and PD‐like behaviors. These changes were blunted in IL‐1R1 deficient mice. Further studies found the LPS treatment inhibited IL‐1R1‐dependent autophagy in the OB. These results suggest that IL‐1β/IL‐1R1 signaling in OB play a vital role in the induction and propagation of aberrant α‐Syn, which may ultimately trigger PD pathology.